Comparison of fuel consumption and recoverable energy according to NEDC and WLTP cycles of a vehicle - Karamangil, M. İhsan and Tekin, Merve (CT&F - Ciencia, Tecnología y Futuro, 2022)
Since 1997, the NEDC (New European Driving Cycle) has been used to measure CO2 emissions. However, because this cycle is unable to accurately replicate real-world driving conditions, a new procedure has been developed. The WLTP (Worldwide Harmonised Light Vehicles Test Procedure), which is 10 minutes longer and more dynamic than NEDC, has been used since late 2017. In this paper, fuel consumption, CO2 emissions, and energy demand of these two cycles are compared. The vehicle mathematical model was created in a MATLAB program using vehicle longitudinal motion equations for a light commercial vehicle with a diesel engine. The speed profiles of the commonly used NEDC and WLTP cycles were defined in the model, and the fuel consumption, CO2 emission values, and the total energy values required for each cycle were calculated. Furthermore, the recoverable energy potential of the cycle has been revealed. According to the WLTP cycle, the vehicle's fuel consumption and CO2 emission values were calculated at approximately 11% more than the NEDC cycle. The recoverable energy potential is 2.64 times higher in the WLTP cycle compared to the NEDC cycle. Thus, for vehicle designers, it is a very useful tool that can calculate the fuel and CO2 consumption of a vehicle in 100 km according to certain cycles, based on vehicle parameters.